Pesticides in Vegetable and Food Commodities: Environment and Public Health Concern - Thapa, K; Pant, B R (Journal of Nepal Health Research Council, 2015)
Haphazard use of pesticides in the field and stored food commodities for the control of insect and pest has been a serious problem from view of environment and public health.  The nutritional value of these is suppressed due to addition of toxins. The increased trend of Non communicable disease and communicable diseases may have close relation with the nutritious value and life styles associated with. The impacts on health should be considered as important issues from the view of public health. The article gives emphasis on organic farming & Integrated Pest Management (IPM) to minimize the harm of chemicals. It is deemed essential to think again about the current trend of malnutrition & obesity overweight among the Nepalese people and relationship with pesticides on the foods and vegetables.   Keywords: foods; health impacts; pesticides; public health; vegetables.